Human Resource Competency, Economic Potential and Village-Based Enterprises' Productivity: The Mediating Role of Governance - Ida Bagus Putu Purbadharmaja; Putu Yudi Setiawan; M. Rudi Irwansyah; Bagus Shandy Narmaditya (Asian Journal for Public Opinion Research)
This study aims to investigate the relationship between human resource competency, economic potential, and productivity of village-based enterprises, as well as understand the role of governance in mediating this relationship. This study was conducted in several village-based enterprises in Bali, Indonesia and the data were collected using questionnaires. Furthermore, the collected data were analyzed quantitatively using partial least analysis to confirm the relationship between variables. The findings indicate that human resource competency has an impact on governance, but it failed to explain the productivity of village-based enterprises. In addition, economic potential can have an impact on the governance and productivity of village-based enterprises in Bali, Indonesia. This study also showed a robust link between governance and productivity. Lastly, based on the statistical analysis, it was found that governance can mediate the relationship between human resource competency, economic potential, and productivity of village-based enterprises.